PENENTUAN SUHU PERMUKAAN LAUT DAN KONSENTRASI KLOROFIL UNTUK PENGEMBANGAN MODEL PREDIKSI SST/FISHING GROUND DENGAN MENGGUNAKAN DATA MODIS - Suwargana, Nana; Arief, Muchlisin (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2004)
Research on oceanography application either in global scale or mesoscale requires sea surface temperature observation and imagery ocean color from satellite. LAPAN has done some observation on oceanography by using NOAA-AVHRR Satelit Data, as in determining the implemented sea surface temperature to determine fishing ground (fish catching area), etc. However, by launching the new satellite that TERRA Satellite that brings spectral multi sensor (MODIS data/Moderate Imaging Spectroradiometer), the research is tried by using MODIS data. The aim of this research is to determine sea surface temperature distribution and to see klorofill content distribution by using MODIS data in order to determine the phenomena of upwelling and front. The method that is carried out in this research is by using algoritma from (Minnet, 2001) for sea surface temperature and (Relly, 1998) for klorofill concentration, and to converse the radiance value [band 21 and band 32] of MODIS image to sea surface temperature value and conversion of two-channel ratio of visible area [band 9 and 12] to the value of the klorofill content. The result of the research shows that algoritma development model whether for sea surface temperature or cholorophyll concentration gives the value of spatial distribution that generally is close to what has been obtained from NOAA-AVHRR satellite data or SeaWhifs. However, the above result still require the detailed development and validation.